Legal Education for Property Consumers: Risk Analysis of the Pre-Project Selling System in the Case of Developer Adhiland - Sahlan Roy Martua Hasibuan; Imam Kuswahyono; D Djumikasih (CV. Media Digital Publikasi Indonesia, 2025)
This research analyzes the legal implications and consumer protection in the purchase of boarding houses with Pre Project Selling (PPS) system by Developer Adhiland in Malang. The juridical-sociological empirical method reveals discrepancies between Adhiland's practices and the Consumer Protection Law and PUPR Regulation, which require developers to fulfill requirements such as IMB, land ownership, and a minimum development progress of 20%. The findings show that Adhiland often violates these provisions, such as the absence of IMB and the unclear schedule of the sale deed, which creates legal uncertainty and the risk of default. Consumers have the right to seek redress through BPSK (mediation/arbitration) or litigation, although the court route is rarely chosen due to its complexity and high cost. The research concluded three critical points: 1) Adhiland is operating PPS in a non-compliant manner, 2) Violations are potentially subject to administrative/criminal sanctions, and 3) Buyers can file a lawsuit despite facing procedural obstacles. Recommendations The research emphasizes two aspects: first, stricter government oversight of PPS practices, including verification of permits and development progress. Second, educating buyers about their legal rights to prevent losses. These findings are relevant as material for evaluating property consumer protection policies.